Hubungan Kekeliruan Informasi Tentang Coronavirus Diseases 2019 terhadap Perilaku Penduduk di Kelurahan Titi Kuning - Aprilia, Daniella; Permatasari, Ranti (UI Scholars Hub, 2022)
Background: Along with the increasing cases of COVID-19, the spread of misinformation (infodemic) in the community has also increased. With this infodemic, efforts to deal with COVID-19 will be increasingly difficult. Objective: This study aimed to determine the relationship between misinformation about COVID-19 circulating and the behavior of the residents of Titi Kuning Village in dealing with it. Method: The method used in this study is an analytical study with a cross-sectional design. The population and sample of this study came from residents of Titi Kuning Village, Medan Johor District, Medan City, North Sumatra Province. Sampling collection used a consecutive sampling method with 100 samples. This study used primary data by collecting residents in one place, distributing direct questionnaires, and asking research subjects to fill them out. Results: The most sources of information on COVID-19 for respondents came from social media (26.5%) and the internet (25.8%). The number of misinformation on COVID-19 is moderate (59%). The behavior of residents in Titi Kuning Village regarding COVID-19 was classified as decent (72%). Conclusion: There is no significant relationship between misinformation (infodemic) about COVID-19 and behavior related to COVID-19 among residents in Titi Kuning Village, Medan Johor District, Medan City.